“Now You Have Become Doctors”: Lady Health Workers' Experiences Implementing an mHealth Application in Rural Pakistan - Kinshella, Mai-Lei Woo; Sheikh, Sana; Bawani, Sohail; La, Michelle; Sharma, Sumedha; Vidler, Marianne; Magee, Laura A.; Dadelszen, Peter von; Bhutta, Zulfiqar; Qureshi, Rahat Najam; Payne, Beth A.; , The CLIP Working Group (Frontiers in Global Women's Health, 2021)
Background: PIERS on the Move (POM) is a mobile health application developed to support community health workers identification and management of women at risk of adverse outcomes from pre-eclampsia. The objective of this study was to evaluate the impact of using POM in Pakistan on Lady Health Workers’ (LHWs) knowledge and self-efficacy related to caring for women with pre-eclampsia, and their perception of usefulness of the tool. Methodology: An evaluation was designed for health care workers involved in the Community-Level Intervention for Pre-eclampsia (CLIP) cluster randomized trial from 2014-2016 in Sindh Province, Pakistan (NCT01911494). A semi-structured focus group guide was developed based on the Technology Acceptance Model (TAM), which theorizes that an individual’s behavioural intention to use a system is determined by perceived usefulness and ease of use. Preliminary qualitative analysis was undertaken by the Pakistan and Canadian teams to create a coding framework for full qualitative analysis, which was completed using NVivo12. Results: Three key informant interviews were conducted with two Lady Health Supervisors and one Senior Medical Officer. Sixty-two LHWs were included in three focus group discussions. LHWs found the POM app easy to use and useful for their work as a helpful repository for maternal health information and guiding counselling and management of pre-eclampsia. LHWs reported increased knowledge and confidence in their work. Availability of clinical homecare, including postpartum, was felt to positively impact healthcare provided to pregnant and postpartum women. Potential community level impacts included strengthening relationships between health care providers and communities and between LHWs and the health system. LHWs shared reports of earlier care-seeking and increased awareness of maternal health issues by community members. Conclusions: LHWs carry a large burden of responsibility for community health in rural Pakistan and appreciated the investment in their skills and capacity during the CLIP trial with the POM app. Investing in communications technology for community health workers through improved referrals and follow up may strengthen cohesiveness of the health system overall.